Break of reciprocity on the light scattered by a disordered atomic cloud - Magnani, Pedro Henrique Nantes (2024)
This study delves into interference phenomena, specifically exploring interference patterns arising from light scattered by a disordered assembly of cold atoms. The investigation focuses on disrupting optical path reciprocity within a mirror-assisted Coherent BackScattering setup (mCBS), where light scattered by a large cold atomic cloud interferes with its mirror image. The introduction of non-commuting polarizing optics, such as a birefringent mirror and a half-waveplate, reveals a reduction in contrast in the fringes, uncovering a geometric interpretation on the Poincaré sphere. The study examinated intensity profiles and fringes in two different clouds: a magneto-optical trap (MOT) based on the 689 nm transition and another on the 461 nm transition. The analysis involves fitting measured curves and understanding contrast reduction and phase shifts related to polarization changes. The study also explored the Pancharatnam-Berry phase, determining its impact on reciprocity in the system influenced by factors like finite optical density and the saturation parameter. The non-commutation of polarizing optics emphasizes the dependence of reciprocity on specific values of parameters. The mCBS configuration offers a distinctive setup, enabling the straightforward introduction of such non-commutative optics. Despite uncertainties, the agreement between theoretical predictions and experimental data validates the robustness of the study, providing valuable insights into the intricate interplay of experimental parameters and system characteristics. In a broader context, the experimental findings underscore the vectorial nature of light as a powerful tool for manipulating the reciprocity of interfering paths, impacting interference while preserving spectral and spatial coherence. This study opens avenues for further exploration in this complex and nuanced research domain.